Improving the Pronunciation Ability of The Second Semester Students of Muhammadiyah University of Sidenreng Rappang Through Phonetic Symbols - Ilham (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2021)
The objective of the research was to find out : (1) whether or not phonetic symbols influence pronunciation ability of the second-semester students of Muhammadiyah University of Sidenreng Rappang and (2) whether or not the students interested in the use of phonetic symbols in teaching and learning pronunciation of the second-semester students of Muhammadiyah University of Sidenreng Rappang. This research applied a Pre-experimental method that applied one group pre-test and post-test. The subject of the research was the second-semester students of Muhammadiyah University of Sidenreng Rappang in the academic year 2018/2019. The total population was 30 students that gather in one class and the population was taken as samples by the total sampling technique. The data of the research were collected by using two kinds of instruments, namely pronunciation test, and questionnaire. The pronunciation test was used to obtain data on the students’ pronunciation ability and the questionnaire was used to know the students’ interest in teaching and learning pronunciation through phonetic symbols.